A simulation study of hybrid solar drying chamber for agriculture product - Mohd Rosli, Mohd Afzanizam; Wong, Kar Hao; Ponnaiyan, Jayaprakash; Herawan, Safarudin Ghazali; Hussain, Faridah (Penerbit Akademia Baru, 2024)
Hybrid solar drying chamber is an application that is widely used today for agriculture products because it can promise the hygiene of the product. However, drying chambers nowadays still lack uniformity in drying products within a drying chamber, leading to food wastage and compromised product quality. This study aims to design an innovative hybrid solar drying chamber system and investigate the uniformity of temperature and velocity within the chamber using Computational Fluid Dynamics (CFD). The methodology involves validating the simulation results by comparing them with existing journal data, with a validation error of less than 5%. A new design is proposed after the validation process, considering factors such as tray arrangement and air inlet size. The results show that a tray arrangement with 0.20 m spacing between each tray provides better uniformity in temperature and air velocity distribution compared to other arrangements. Additionally, an inlet size of 0.05 m2 demonstrates the most suitable temperature distribution for drying purposes, falling within the ideal range of 318 K to 343 K. The study showed that the performance of the drying chamber under different operating conditions has consistent temperature distribution and is suitable for uniform drying. Overall, the proposed hybrid solar drying chamber system offers improved temperature control and uniformity for effective drying process.